2022
DOI: 10.3390/pharmaceutics14061151
|View full text |Cite
|
Sign up to set email alerts
|

Why Use Adipose-Derived Mesenchymal Stem Cells in Tendinopathic Patients: A Systematic Review

Abstract: The aim of the present systematic review was to provide a clear overview of the clinical current research progress in the use of adipose-derived mesenchymal stem cells (ASCs) as an effective therapeutic option for the management of tendinopathies, pathologies clinically characterized by persistent mechanical pain and structural alteration of the tendons. The review was carried out using three databases (Scopus, ISI Web of Science and PubMed) and analyzed records from 2013 to 2021. Only English-language papers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Another cell therapy that has been used in the treatment of tendinopathies is the use of mesenchymal stem/stromal cells (MSC) from a variety of tissue sources including bone marrow, adipose tissue, and other sources including both allogeneic as well as autologous sources. Such studies have been recently reviewed extensively (61)(62)(63)(64)(65)(66)(67). As reviewed by Di Matteo et al (61) and Mirghaderi et al ( 65), often such MSC preparations are used in conjunction with PRP.…”
Section: Biologics and Tendinopathiesmentioning
confidence: 99%
“…Another cell therapy that has been used in the treatment of tendinopathies is the use of mesenchymal stem/stromal cells (MSC) from a variety of tissue sources including bone marrow, adipose tissue, and other sources including both allogeneic as well as autologous sources. Such studies have been recently reviewed extensively (61)(62)(63)(64)(65)(66)(67). As reviewed by Di Matteo et al (61) and Mirghaderi et al ( 65), often such MSC preparations are used in conjunction with PRP.…”
Section: Biologics and Tendinopathiesmentioning
confidence: 99%
“… 2 Tendinopathy can also occur in some people due to age, obesity, chronic smoking, alcohol abuse, and the use of glucocorticoids for prolonged periods due to illness or work that puts the tendons under excessive strain. 3 , 4 , 5 In recent years, epidemiological studies have revealed that tendinopathy is increasingly prevalent in both sports medicine and orthopaedic clinical settings, resulting in substantial medical costs and disability. 4 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…These are characterized by both micro- and macro-structural tendon alterations, leading to prolonged mechanical pain. 1 4 …”
Section: Introductionmentioning
confidence: 99%